A new species of Astyanax Baird & Girard (Characiformes: Characidae) from western Chapada Diamantina, Bahia, Brazil - Burger, Rafael; Carvalho, Fernando R.; Zanata, Angela M. (Zootaxa, 2019)
A new species of Astyanax from the upper rio Paraguaçu basin, Chapada Diamantina, Bahia, Brazil, is described. Astyanax sincora shares characters currently used to define the Astyanax scabripinnis species complex, as highest body depth approximately at vertical through pectoral-fin midlength and a low number of branched anal-fin rays (13–17). It differs from its congeners by a combination of characters, including eight branched dorsal-fin rays, six branched pelvic-fin rays, presence of bony hooks in pectoral and anal fins of males, dark midlateral line or stripe initiating posteriorly to the vertically elongate humeral blotch, and by the presence of 30–35 scales in the median longitudinal series. The generic positioning of the new species and some polymorphic morphological characters in Astyanax are briefly discussed. The degree of completeness of the lateral line in Hyphessobrycon balbus is discussed. [Species Zoobank registration: urn:lsid:zoobank.org:pub:D708FE7E-3FB5-4729-B438-779717F7ED1A]